Butyrate inhibits human mast cell activation via epigenetic regulation of FcεRI‐mediated signaling. Issue 8 (24th April 2020) - Folkerts, Jelle; Redegeld, Frank; Folkerts, Gert; Blokhuis, Bart; van den Berg, Mariska P. M.; de Bruijn, Marjolein J. W.; van IJcken, Wilfred F. J.; Junt, Tobias; Tam, See‐Ying; Galli, Stephen J.; Hendriks, Rudi W.; Stadhouders, Ralph; et al.
Abstract: Background: Short‐chain fatty acids (SCFAs) are fermented dietary components that regulate immune responses, promote colonic health, and suppress mast cell–mediated diseases. However, the effects of SCFAs on human mast cell function, including the underlying mechanisms, remain unclear. Here, we investigated the effects of the SCFAs (acetate, propionate, and butyrate) on mast cell–mediated pathology and human mast cell activation, including the molecular mechanisms involved. Method: Precision‐cut lung slices (PCLS) of allergen‐exposed guinea pigs were used to assess the effects of butyrate on allergic airway contraction. Human and mouse mast cells were co‐cultured with SCFAs and assessed for degranulation after IgE‐ or non–IgE‐mediated stimulation. The underlying mechanisms involved were investigated using knockout mice, small molecule inhibitors/agonists, and genomics assays. Results: Butyrate treatment inhibited allergen‐induced histamine release and airway contraction in guinea pig PCLS. Propionate and butyrate, but not acetate, inhibited IgE‐ and non–IgE‐mediated human or mouse mast cell degranulation in a concentration‐dependent manner. Notably, these effects were independent of the stimulation of SCFA receptors GPR41, GPR43, or PPAR, but instead were associated with inhibition of histone deacetylases. Transcriptome analyses revealed butyrate‐induced downregulation of the tyrosine kinases BTK, SYK, and LAT, critical transducers of FcεRI‐mediated signals that are essential for mast cell activation. Epigenome analyses indicated that butyrate redistributed global histone acetylation in human mast cells, including significantly decreased acetylation at the BTK, SYK, and LAT promoter regions. Conclusion: Known health benefits of SCFAs in allergic disease can, at least in part, be explained by epigenetic suppression of human mast cell activation. Abstract : Short‐chain fatty acids suppress primary human mast cell activation via HDAC inhibition and not via PPAR or GPR signaling. Butyrate induces transcriptional changes of genes important for signaling and activation of human mast cells. Butyrate triggers a redistribution of global H3K27 acetylation levels, leading to decreased acetylation at the transcription start site of genes encoding key FcεRI‐mediated signaling molecules.